Edema agudo de pulmão de pressão negativa como complicação grave de síndrome de apneia obstrutiva do sono em crianças. Relatos de casos - Silva, Érico V. C. M. [UNESP]; Chi Sakai, Andrea P. [UNESP]; Bonatto, Rossano César [UNESP]; Weber, Silke Anna Theresa [UNESP] (My University, 2010)
Introduction: Obstructive sleep apnea syndrome is related to cardiopulmonary complications in children. It is important to know its patophysiology and possible complications to help reduce risks in this group. Aims: To report three cases of severe cardiorespiratory complications of obstructive sleep apnea managed in the intensive care unit (ICU). Case report: Two children with no previous diagnosis of obstructive sleep apnea syndrome suffered acute congestive heart failure and acute lung oedema with need of ICU and improved after adenotonsillectomy. In a third case, the patient had acute lung oedema as a complication after adenotonsillectomy. Conclusions: Paediatricians and otolaryngologists must be aware of the clinical manifestations of severe sleep apnea. Early referring to treatment and special attention at pre and post surgical periods are essentials to avoid serious complications.
Acute negative pressure lung oedema as a severe complication of obstructive sleep apnea syndrome in children. Case reports
Keywords: Acute lung oedema; Adenotonsillectomy; Obstructive sleep apnea; bronchodilating agent; didanosine; lopinavir plus ritonavir; stavudine; acute disease; acute negative pressure lung edema; adenotonsillectomy; anasarca; artificial ventilation; case report; child; congestive heart failure; dyspnea; electrocardiogram; fiberscope endoscopy; human; Human immunodeficiency virus infection; intensive care unit; lung auscultation; lung edema; male; preschool child; respiratory failure; school child; sleep apnea syndrome; thorax radiography; treatment outcome